Experimental study on ignition behavior of pulverized coal particle clouds in a turbulent jet. (1st March 2016) - Xu, Kailong; Wu, Yuxin; Wang, Zhennan; Yang, Yanmei; Zhang, Hai
Graphical abstract: Abstract: Ignition behaviors of pulverized coal particle clouds in a jet with different turbulent intensity, O2 concentration and coal concentration were experimentally studied using an entrained flow reactor. Mie scattering technique and high-speed cameras were employed to record the particle motions and flame behavior. Results revealed that a cloud flame consisted of a number of parcel flames and stripe flames, which were located in the center and around boundary of the cloud flame, and resulted by the burning of the evolved volatile matter or the clusters of fine fuel particles, and the burning of the single particles respectively. As Reynolds number of the primary flow increased, the cloud flame changed from narrow and structured to wide and turbulent. At the same time, the particle dispersion became more intensive, leading to a lower flame incandescence. The increase of O2 concentration in the primary or secondary flow promoted ignition of cloud flames. For laminar cloud flame, ignition distance was more sensitive the O2 concentration in the primary flow, and a minimum value was found at certain coal concentration, but for turbulent cloud flame, ignition distance was shorter, and no obvious non-monotonic trend was found over the tested coal concentration range.